Ising model on the Cayley tree of second order with left and right interactions - Ganikhodjaev, Nasir; Ibrahim, Huda Husna (American Institute of Physics Inc., 2016)
In this paper we consider Ising model on the semi-infinite Cayley tree of second order with left and right interaction and investigate the problem of phase transition for this model.